Locality in Makoto Shinkai’s Kimi no Na wa: Negotiating Japanese Youth Identity - Muammar Kadafi; Shofi Mahmudah Budi Utami (IZUMI, 2021)
Japan becomes one of the countries that has been producing worldwide popular culture, namely through anime. Besides its popularity which attracts wider audiences, anime cultivates cultural content as it is also found in popular anime entitled “Kimi no Na wa”. Aside from its popular culture, Japan has undoubtedly been known for its ‘high culture’ products such as haiku or Zen, to which Japanese identity is attached. Then, the content of Japanese locality performed in the anime highlights some crucial issues related to Japanese identity, including the problematic relationship between traditionality and modernity, generations, and genders. Thus, the local content in the anime is interesting to scrutinize how traditional values are depicted and negotiated concerning Japanese identity. Since this study is descriptive-qualitative research, it answers the problem by describing the phenomenon and employing the interpretative method by Hall’s concept of identity. The selected data related to locality and identity obtained from the movie and poster are grouped and approached by Hall’s semiotic representation to see the relation to its significations. Finally, this brings out the interpretation of the data indicating that the anime portrays the ‘return’ to local culture. It is referred to as ‘nihonjinron’, which is particularly emphasized in youth life. Through this film, the identity is negotiated. The characters (Taki and Mitsuha) perform post-modern subjects; a case in point accepts the changes as they develop their identity in the current era.